Cross talk between paxillin and Rac is critical for mediation of barrier-protective effects by oxidized phospholipids - Birukova, Anna A. (American Physiological Society, 2008)
We previously reported that the barrier-protective effects of oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphocholine (OxPAPC) on pulmonary endothelial cells (ECs) delineate the role of Rac- and Cdc42-dependent mechanisms and described the involvement of the focal adhesion (FA) protein paxillin in enhancement of the EC barrier upon OxPAPC challenge. This study examined a potential role of paxillin in the feedback mechanism of Rac regulation by FAs in OxPAPC-stimulated ECs. Our results demonstrate that OxPAPC induced Rac-dependent, Rho-independent peripheral accumulation of paxillin-containing FAs and time-dependent paxillin phosphorylation. Molecular inhibition of Rac decreased association of paxillin with the Rac-specific guanine nucleotide exchange factor β-PIX. Molecular inhibition of paxillin also attenuated OxPAPC-induced enhancement of adherens junctions critical for the EC barrier-protective response, accumulation of vascular endothelial cadherin in the membrane fractions, and decreased activation of Rac and its effector p21-activated kinase (PAK1). Expression of paxillin with a mutated PAK1-dependent phosphorylation site (S273A) attenuated OxPAPC-induced PAK1 activation and the EC barrier-protective response. These results suggest that PAK1-specific paxillin phosphorylation at Ser(273) is critically involved in the positive-feedback regulation of the Rac-PAK1 pathway and may contribute to sustained enhancement of the EC barrier caused by oxidized phospholipids.